2014
DOI: 10.1088/0067-0049/215/2/22
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Virgo Cluster Catalog

Abstract: We present a new catalog of galaxies in the wider region of the Virgo cluster, based on the Sloan Digital Sky Survey (SDSS) Data Release 7. The Extended Virgo Cluster Catalog (EVCC) covers an area of 725 deg 2 or 60.1 Mpc 2 . It is 5.2 times larger than the footprint of the classical Virgo Cluster Catalog (VCC) and reaches out to 3.5 times the virial radius of the Virgo cluster. We selected 1324 spectroscopically targeted galaxies with radial velocities less than 3000 km s −1 . In addition, 265 galaxies that h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
182
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(199 citation statements)
references
References 67 publications
7
182
0
Order By: Relevance
“…The Extended Virgo Cluster Catalogue (EVCC, Kim et al 2014) provides the redshifts and positions on the sky of 1589 galaxies in a footprint of 725 deg 2 centred on M87, extending to 3.5 times the cluster virial radius. The redshifts are compiled from the SDSS DR7 release and the NASA Extragalactic Database (NED), and each object is classified as either a certain cluster member, a possible member or a background source based on morphological and spectroscopic criteria.…”
Section: Satellite Galaxiesmentioning
confidence: 99%
“…The Extended Virgo Cluster Catalogue (EVCC, Kim et al 2014) provides the redshifts and positions on the sky of 1589 galaxies in a footprint of 725 deg 2 centred on M87, extending to 3.5 times the cluster virial radius. The redshifts are compiled from the SDSS DR7 release and the NASA Extragalactic Database (NED), and each object is classified as either a certain cluster member, a possible member or a background source based on morphological and spectroscopic criteria.…”
Section: Satellite Galaxiesmentioning
confidence: 99%
“…Despite their relative low scatter, these relations are unfortunately not sufficiently accurate for an unambiguous identification of cluster members and thus need to be combined with statistical tests. These scaling relations are determined using either the Extended Virgo Cluster Catalogue (EVCC, Kim et al 2014) or the GUViCS catalogue of galaxies analysed in Boselli et al (2014a). The EVCC catalogue was chosen because it includes galaxies at the same distance as Virgo (vel ≤ 3000 km s −1 ), it has both star forming and quiescent galaxies, and provides structural parameters comparable to those listed in the GUViCS point-like catalogue of Voyer et al (2014).…”
Section: Statistical Correction Based On Galex-sdss Scaling Relationsmentioning
confidence: 99%
“…This can be done either by using the accurate morphological classification given in the VCC or in the EVCC (Kim et al 2014), or by using the colour of galaxies as in Boselli et al (2014a). As in our previous work, we select galaxies belonging to the red sequence, the green valley, and the blue cloud Notes.…”
Section: Luminosity Function As a Function Of Morphological Typementioning
confidence: 99%
“…The Virgo Cluster, instead, is still growing. Subclusters around the ellipticals M86 and M49 (whose systemic velocities are, respectively, −181 and 950 km s −1 , Kim et al 2014) are merging with the main cluster around the central elliptical M87. Several H I imaging surveys of the cluster revealed that the H I discs of its central late-type galaxies are truncated to well within the optical discs, suggesting that ICM-ISM interactions play an important role in driving the evolution of galaxies in the inner region of the cluster (Warmels 1988;Cayatte et al 1990;Chung et al 2009;Boselli et al 2014).…”
Section: Introductionmentioning
confidence: 99%